Deposition of bodily chemical components in the carcass of tilapia (oreochromis sp.) strains - Allaman, Ivan Bezerra; Reis Neto, Rafael Vilhena [UNESP]; Fonseca de Freitas, Rilke Tadeu; Rosa, Priscila Vieira; Lago, Aline de Assis; Costa, Adriano Carvalho (Univ Federal Lavras-ufla, 2014)
The knowledge of how animals deposited chemical components as water, protein, fat and ash in the carcass is importance for the formulation of a balanced diet, allowing maximum performance with a low environmental impact. So, the study was carried out to evaluate the influence of different tilapia strains (Chitralada, Commercial, Red and Universidade Federal de Lavras [UFLA]) on the deposition of bodily chemical components in the carcass. The bodily components analyzed were water, protein, fat and ash. For the determination of the bodily chemical deposition curves by age, the exponential, Brody, logistic, Gompertz and von Bertalanffy models were adjusted. The Commercial and UFLA strains deposited water at a faster speed (P<0.05) compared with the remaining strains. As for protein, the Red strain had a lower estimated maturity weight (49.37 g), and was more precocious (202 days) with regard to maximum deposition in comparison to the other strains (Chitralada, UFLA and Commercial) in which there was an estimated maturity weight of 231.5 g and maximum depositionfor 337 days. There were no differences (P>0.05) for the logistic model parameter between Red, UFLA and Commercial strains for fat, which presented a maximum fat deposition (0.23 g) at 310 days of age. Regarding ash deposition, the Commercial strain presented a higher maximum deposition (0.10 g) at 337 days, occurring later than the other strains that presented maximum deposition (0.033g) at 254 days of age. Thus, it was concluded that the genetic strains evaluated differ in chemical deposition curves of water, protein, fat and ash.

O conhecimento de como os animais depositam componentes químicos como água, proteína, gordura e cinzas na carcaça é importante para a formulação de uma dieta equilibrada, permitindo o máximo desempenho com baixo impacto ambiental. Logo, o trabalho foi conduzido, com o objetivo de avaliar a influência de diferentes linhagens de tilápia sobre a deposição de componentes químicos na carcaça. Os componentes corporais analisados foram água, proteína, gordura e cinzas. Para a determinação das curvas de deposição química corporal em função da idade foram ajustados os modelos exponencial, Brody, logístico, Gompertz e vonBertalanffy. Houve ajuste apenas do modelo exponencial para a água, tendo as linhagens UFLA e Comerciais as que depositaram numa velocidade mais rápida (P<0,05) em relação às demais linhagens. Quanto à proteína, a linhagem Vermelha foi a que teve menor peso à maturidade, estimado (49,37g) e foi mais precoce quanto à deposição máxima em relação as outras linhagens (Chitralada, UFLA e Comercial), no qual obtiveram peso a maturidade estimada em 231,5g e deposição máxima aos 337 dias de idade. Não houve diferença (P>0,05) dos parâmetros do modelo logístico entre as linhagens Vermelha,UFLA e Comercial para extrato etéreo, sendo a deposição máxima (0,23 g) aos 310 dias de idade. Em relação à deposição de cinzas, a linhagem Comercial teve maior deposição máxima (0,10 g) e, aos 337 dias de idade, sendo mais tardia em relação as outras linhagens que obtiveram deposição máxima de 0,033 g, aos 254 dias de idade. Portanto, conclui-se que as linhagens genéticas avaliadas diferem quanto às curvas de deposição química de água, proteína, extrato etéreo e cinzas.
Keywords: Bodily components; nonlinear models; fish; growth; Composição corporal; Modelos não-lineares; Peixe; Crescimento